Paciente con Diagnóstico de Absceso Pulmonar Asociado con Gingivitis - Malave Arias, Kenia Lucciola (2018)
Pulmonary abscesses are defined as circumscribed and suppurative processes of the pulmonary parenchyma that are caused by pyogenic germs; which results in a necrotic cavity of pus. This is caused by a microbial infection whose frequent etiological focus is the aspiration of anaerobic pharyngeal gold germs. The best anatomical definition is given by tomography, which often helps in the diagnosis of the pathology. The most frequent clinical manifestations are fever, nocturnal hypersupersis, pleuritic pain, abundant purulent expectoration of ashen or chestnut color. Among the bacterial infections, anaerobes, mycobacteria, fungi, parasites and other bacteria stand out: Estrectococus anaeroibios, Nocardia, Legionella, Enterobacteriaceae, Staphylococcus aureus, fusobacterium. The treatment is antibiotic therapy and for anaerobic abscesses it is clindamycin and should last three to six weeks, among others. Therefore, our main objective of the work was based on applying the process of nursing care to a patient of 73 years, with pulmonary abscess associated with gingivitis, in order to provide timely care and specific treatment to avoid complications and reach to the death. The nursing professional socializes and interacts with the patient to obtain essential information for the conformation of nursing diagnoses that give an understanding of the needs of the patient. It should be noted that the goal of nursing is to promote care, assistance, empathy, safety, education, and provide quality care and warmth for humanity.